EPA's Safety Measures for Aluminum and Magnesium Phosphide Fumigants - Frederick M. Fishel (EDIS)
PI228, a 2-page illustrated fact sheet by F.M. Fishel, outlines new EPA restrictions on aluminum and magnesium phosphide products used to control burrowing rodents. Includes additional sources of information. Published by the UF Department of Agronomy, May 2010.